Efficient disentanglement of polycarbonate melts under complex shear field. (26th June 2020) - Wang, Yingxiong; Liu, Minjing; Chen, Jin; Luo, Jiaxu; Min, Jie; Fu, Qiang; Zhang, Jie
Abstract: Disentanglement is potentially a feasible method to improve the processability of polymers without any additives. But there still lacks the methods to efficiently prepare "in-pellet" disentangled polymers. To realize the large-scale production of disentangled pellets, we firstly designed a novel Polymer Melt Disentanglement Machine (PMDM), which can uniquely impose complex shear field (superposition of rotational shear and oscillatory shear) on polymer melt to induce disentanglement. Then, the disentangled polycarbonate pellets were prepared by PMDM under rotational shear, oscillatory shear and complex shear respectively. Finally, we compared the disentanglement effect of those three shear modes and the results show that the sample disentangled by complex shear field has a lower zero-shear viscosity and a higher melt flow rate compared with the samples disentangled by other two shear modes. Besides, the processing temperature and pressure of the disentangled pellets can be reduced by 20 °C and 25% respectively compared with the raw pellets. Complex shear field can efficiently disentangle polymer melt, which indicates its application prospect to improve the processability of the engineering plastics with high melt viscosity, such as polycarbonate et al., by a large-scale production of "in-pellet" disentangled materials via PMDM prior to processing. Graphical abstract: Image 1 Highlights: A novel "Polymer Melt Disentanglement Machine (PMDM)" was designed. Disentangling effect of different shear fields on polycarbonate melt was compared by using PDMD. Disentangled polycarbonate pellets can be processed with lower melt temperature and injection pressure.